2019
DOI: 10.1080/02670836.2018.1466418
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of deformed α′(α″) martensitic phase in Ti–6Al–4V alloy

Abstract: The process of martensitic α′( α″) phase decomposition in titanium alloys has not been sufficiently characterised in the literature – especially in terms of plastically deformed martensite. The research results of water-quenched Ti–6Al–4V alloy, subsequently cold deformed in compression test and tempered at the temperature range of 600–900°C for 1 and 2 h were presented in the paper. Light and scanning electron microscopy observations revealed the influence of plastic deformation on tempered martensite laths m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…4). Microstructure in outer parts of compressed specimens -called "undeformed zones 1 " -is typical for martensite decomposition in Ti-6Al-4V alloy [12]. No significant changes in martensitic microstructure were detected by light microscopy method after deformation at 600ºC (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…4). Microstructure in outer parts of compressed specimens -called "undeformed zones 1 " -is typical for martensite decomposition in Ti-6Al-4V alloy [12]. No significant changes in martensitic microstructure were detected by light microscopy method after deformation at 600ºC (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…It is believed that the product of martensite decomposition in two-phase titanium alloys is a mixture of a and b phases [1][2][3]. Using XRD method, in previous investigation [12], it was confirmed that b phase was formed after 1 h tempering at the temperature range of 600-900ºC. In presented research XRD measurement were conducted in the central part of compressed specimens -in or close to the FLZ.…”
Section: A) B)mentioning
confidence: 89%
See 1 more Smart Citation
“…Although stress relief is shown to improve on increasing temperature (Fig 4c), there is little improvement between 700 and 750°C as the process is effectively complete. Whilst this may appear beneficial in terms of reducing residual stress, aging at such temperatures would lead to thickening of secondary α and in turn, reduced strength [14]. Whilst annealing is commonly conducted in this region, lower temperatures are often selected for aging treatments.…”
Section: Resultsmentioning
confidence: 99%
“…The microstructure and mechanical behavior of TC4 alloy are very sensitive to the history of the thermomechanical deformation and thermochemical treatment [6][7][8][9]. Ahmed [10] found that the transformation mechanism of TC4 alloy is complete martensite, massive transformation and diffusion transformation with the cooling rate decreasing from 525 • C/s to 1.5 • C/s.…”
Section: Introductionmentioning
confidence: 99%